Comparative Analysis of the Suspected Heparin‐Induced Thrombocytopenia Level in Korea. Issue 4 (9th August 2017) - Kim, Hun‐Sung; Kim, Hyunah; Jeong, Yoo Jin; Lee, Hyunyong; Yim, Hyeon Woo; Kim, Ji il; Moon, In Sung; Kim, Jang‐Yong
Abstract: The primary objective of our study was to evaluate the frequency of suspected heparin‐induced thrombocytopenia (HIT) among patients treated with different formulations of heparin and investigate the factors that affect the incidence of HIT. This study is an electronic medical record (EMR)‐based large‐scale retrospective cohort study conducted from 2009 to 2014 in Korea. After hospitalization, patient platelet count was determined before heparin was prescribed, and all platelet count values obtained during hospitalization were extracted. Suspected HIT was estimated by three 4Ts scores (acute thrombocytopenia, timing onset and other possible causes), which when combined yielded a high probability of HIT. Among 6046 patients enrolled in this study, HIT was suspected in 641 cases (10.6%) and a statistically significant increase in HIT incidence rate was observed for three heparins used ( p < 0.001). Dalteparin (HR = 0.55, p = 0.036) and enoxaparin (HR = 0.40, p < 0.001) showed a relatively low HIT incidence rate, compared to unfractionated heparin. Majority of suspected HIT cases (76.9 and 66.7%) occurred in days 8–10 and 5–7 of dalteparin and enoxaparin treatments, respectively. Most of the patients medicated with dalteparin were cancer patients; however, no statistically significant relationship was observed between HIT occurrence and cancer. HIT can cause serious complications, making early diagnosis crucial. Clinical practitioners first prescribing heparin should focus on preventing and detecting complications early by conducting frequent, regular platelet counts before and after heparin administration.